Solar photovoltaic performance monitoring based on IoT - Ali Amran Bin Nasrun (2023)
This research aims to design a low-cost solar photovoltaic performance monitoring based on IoT. Blynk mobile application is chosen as the IoT platform to transfer data from solar panel to the internet and ESP8266 Wi-Fi module is used to create wireless connection between microcontroller and IoT platform. Voltage sensor and ACS712 current sensor are applied as the transducers to sense and measure parameters of solar PV panel voltage and current. Power produced and energy consumed by DC fan are calculated by using voltage and current data. All data are stored in Blynk mobile application which provide live data monitoring. Three trials are conducted to observe the performance of solar PV panel and percentage error between digital multimeter measured values and IoT uploaded values are calculated. The result revealed that the prototype works well to monitor solar PV panel as the percentage error is low.